Intracranial hemorrhage in the era of the “direct” oral anticoagulants - Ileana Raluca Nistor; Leonida Gherasim (Romanian Journal of Neurology, 2019)
Intracranial hemorrhage (ICH) is the most severe complication in patients treated with oral anticoagulants (OACs). Duration of anticoagulant therapy and poor anticoagulation control are important factors for hemorrhagic risk. Our purpose is to provide a review of meta-analyses regarding epidemiological data of intracranial hemorrhage, pathogenic conditions associated with IHC in patients treated with OACs, the role of clinical evaluation, data about prognostic and evolution of IHC and the general measures of the IHC treatment.